SUSPENDED SENTENCE WITH CUSTODIAL SUPERVISION IN SERBIA – WHAT DOES CUSTODIAL SUPERVISION INVOLVE? - Nada Đuričić (Pravo, 2023)
Suspended sentence with custodial supervision represents an alternative sanction that the legislation of the Republic of Serbia has known for half a century, but its application is rare because it is ordered in a negligible number of cases. Ordering custodial supervision has its advantages and it can be effective in cases when it is not enough to just sentence a person conditionally nor would it be justified and effective to punish the individual more severely, but it is necessary to ensure some sort of help and support in order to correct the offender’s behavior and deter them from committing criminal acts in the future. In order to better understand this sanction and see how it works in practice, we have analyzed measures of custodial supervision which are most often prescribed in accordance with the committed crimes. The paper uses a statistical and comparative method and analyzes the available literature, as well as the judgments of those courts that in a certain observed period had the largest number of suspended sentences with custodial supervision.